(3TQM ZfjI GdHGMKs - (3GdOeTbqj GdeGpQOjfj, SHW GdeGQOjfj, HOQ GdOjf (B- (3GdZRGd, eMeO Hf eMeO Hf CMeO, (B912 (3g`s ((3YHO GdZfj Hf YHO GdQMef Hf GdUhGa GdejOGfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd (B000 (3eMeO Hf SHW GdeGQOjfj GdMeO ddg QH GdYGdejf hHYO agPG TQM eNJUQ Ydi GdebOeI GdQMHjI aj GdaQGjVs
(3BNQgG (B:s
(3GdCeGLO HGdLje LeY eGLO hgh GdcGed aj GdTQa hGdcQe gh GdUaGJ GdeMehOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 54s
(3eYLe GdeDdajf (B3 / 624s
(3TPQGJ GdPgH (B8 / 30s
(3GdHOQ GdWGdY (B2 / 123s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs